THE IMPACT OF SOCIAL MEDIA USE ON EMPLOYEE WORK PERFORMANCE - Angeloska-Dichovska, Monika; Angeleski, Marjan; Boshkoska, Meri; Petrevska Nechkoska, Renata (Horizons - International Scientific Journal, 2022)
Social media has changed the ways people communicate, express their views, share content, interact and collaborate, by enabling the network effects, information provision, broad audience and outreach, direct connectivity and global situational awareness. The great dominance of social media in the modern way of life, as well as the strong connection of a large number of people with these media and networks, often lead to the fact that a certain part of their working time is spent on social networks. Social media use in the workplace may contribute to both productive as well as unproductive behavior. Research confirms that for certain areas or sectors, the use of social media has a positive impact, especially in the civil society sector. But it is also important to emphasize that in companies where there ispolicy for social media use, it contributes to positive impacts. This paper analyses whether and to what extent social media is used by Macedonian employees during working hours; what are their views on work performance with regards to the social media use; and analyses whether businesses have policies for using social media, which help streamline the benefits while outweighing the downsides? For the purposes of this research, a survey was conducted of 202 employees from the public, private and civil society sectors from the Pelagonia region of the Republic of North Macedonia. This research opens prospective use of findings in managerial and organisational decisions on social media use, as well as in conceptual sense of task diversity for improving work performance in general.